Dari Pekerja ke Wirausaha: Migrasi Internasional, Dinamika Tenaga Kerja, dan Pembentukan Bisnis Migran Indonesia di Taiwan - Paulus Rudolf Yuniarto (Jurnal Kajian Wilayah, 2012)
This paper focuses on the issue of international migration, labor dynamics, and the emergence of independent business (self-employment or entrepreneurship) among Indonesian migrant communities in Taiwan. In addition to contribute the cultural exchange or mix of culture transnationally, the development of cross-border migration also encourages the emergence of social networks and economic activities at regional and global level. The economic dimension that has been linked to international migration issue is dynamics of social change among migrant workers who work for remittances (migrant remittances) to the self optimization (entrepreneurship migrant), that resulted one of them to the creation of one stop service for migrant needs (one stop service). Through observation and interviews conducted to Indonesian entrepreneurs of migrant communities in Taiwan, it shows that: (1) migrants entrepreneurship in recent situation is no longer as a side-job in economic activity, compared to being migrant workers themselves, (2) the financial crisis in 2009 had triggered the growing of migrants entrepreneurship significantly. Therefore, the practice of migrants entrepreneurship has shown its importance not only - to accommodate basic needs, social, and psychological migrant workers, but also to expand the dynamics of Indonesian migrant diaspora living in Taiwan, acculturation among society, speeding the trade flows between regions, and of course increasing economic prosperity among entrepreneurs and migrant workers. Although migrants-entrepreneurs in Taiwan had been criticized more or less for taking advantage the ideas of migrants needs, however this can be understood as a form of adjustment to the businesses they run. Furthermore, migrant entrepreneurship can be seen also as a form of adjustment to the economic potential and socio-cultural they experienced in Taiwan, one of which, by creating a variety of business models and maintain social networks individually or in other groups.Keywords: international migration, Indonesian workers, entrepreneurship.